Perspektif Ekonomi Islam Terhadap Kebijakan Fiskal - Bela Fitriani; Ni’mah Mu’aliyah; Muhammad Azhar Husni; Muhammad Taufiq Abadi (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to describe the Islamic Economic Perspective on Fiscal Policy. The method in this research uses a library research method, namely research whose object of study uses library data. This research was carried out by reading, reviewing and analyzing various existing literature, in the form of journals, articles, books and the internet originating from journals, government and company documentation, and government publications. And in this research the author uses a qualitative approach using secondary data sources. The findings of this literature review study conclude that the Islamic Economic Perspective on Fiscal Policy is a policy that is expected to carry out allocation, distribution and stabilization functions in a country that has certain characteristics of value orientation, ethical and social dimensions in the income and expenditure of an Islamic country. The Islamic taxation system must ensure that only the rich and prosperous groups who have advantages bear the main burden of taxes.